Growth and optical properties of hierarchical flower-like ZnO nanostructures. Issue 3 (15th February 2017) - Lv, Xiangzhou; Liu, Xinchuan; Sun, Qimeng; Wang, Yongqian; Yan, Bing
Abstract: The integration of low dimensions nanoscale building blocks into 3D architectures has attracted great scientific attention. We have obtained the novel hierarchical flower-like ZnO nanostructures self-assembled by nanorods via a facile hydrothermal method. The as-synthesized samples were characterized with various technologies. The field emission scanning electron microscope (FESEM) images indicated that hydroxide ions play a significant role on the formation of hierarchical flower-like ZnO nanostructures. The X-ray diffraction (XRD) result proved that the nanocrystals were well crystallized hexagonal wurtzite structure. A possible growth mechanism of the nanostructures was proposed based on the effects of hydroxide ions. And the TEM imagines provided some important evidence for the proposed growth mechanism. UV–vis adsorption and photoluminescence (PL) spectra results indicated that the obtained ZnO nanostructurs have a good optical-absorption and photoluminescence property. The as-synthesized ZnO nanostructures exhibited superior photocatalytic performance, which was higher than that of commercially available ZnO.